2019
DOI: 10.1109/access.2019.2903127
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Classification Methods for Remote Sensing Images in Urban Built-Up Areas

Abstract: Urban areas have been focused recently on the remote sensing applications since their function closely relates to the distribution of built-up areas, where reflectivity or scattering characteristics are the same or similar. Traditional pixel-based methods cannot discriminate the types of urban built-up areas very well. This paper investigates a deep learning-based classification method for remote sensing images, particularly for high spatial resolution remote sensing (HSRRS) images with various changes and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 40 publications
(25 reference statements)
0
46
0
1
Order By: Relevance
“…In recent years, deep neural network has shown excellent performance in the task of remote sensing image classification and segmentation [16,[39][40][41]. Feature maps output from different layers in neural network reflect different characteristics of remote sensing images.…”
Section: Urban Functional Regions Classification Based On Remote Sensmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, deep neural network has shown excellent performance in the task of remote sensing image classification and segmentation [16,[39][40][41]. Feature maps output from different layers in neural network reflect different characteristics of remote sensing images.…”
Section: Urban Functional Regions Classification Based On Remote Sensmentioning
confidence: 99%
“…Kaliraj [15] researched the Kanyakumari coast in India and exploited Maximum Likelihood Classifier (MLC) algorithm from Landsat ETM+ and TM images to analyze the land use and land cover characteristics. LI [16] investigated a neural network based on deep learning to classify the high spatial resolution remote sensing (HSRRS) images. From the above studies, remote sensing technology can effectively extract the spatial and geographic characteristics of urban functional areas in remote sensing maps [17], which is considered to be the key technology to study the functional alteration of urban land use [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…HSRRS image scene classification problem can be extracted subregions into different semantic classes, and it is a fundamental task and significant for remote sensing applications, such as urban planning, object detection, and natural resource management. Many recent works have demonstrated that CNN is the most successful and widely applied deep learning method, and has been used to make HSRRS image scene classification task [18]. Especially, the DeCNN performs well in semantic features extraction with a lot of convolutional layers and a large amount of training data set.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, deep learning has represented the state of the art in a variety of domains, and CNN as a typical deep learning method, has obtained excellent results in the field of computer vision [22], wireless communications [23], [24] and remote sensing image processing [18]. HSRRS image scene classification based on CNN has achieved excellent results recently.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation